2017
DOI: 10.1093/neuros/nyx298
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Satisfaction After Decompression Surgery for Lumbar Spinal Stenosis

Abstract: This study found smoking, long duration of leg pain, and cancerous and neurological disease to be associated with patient dissatisfaction, whereas good walking capacity at baseline was positively associated with satisfaction after 1 yr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 31 publications
1
42
1
1
Order By: Relevance
“…10,11 In agreement with our results, both studies showed an association between significant improvements in HRQOL and satisfaction with treatment outcomes. 10,11 In addition, Hamilton et al 10 also showed no relation between the occurrence of adverse events (major or minor) and satisfaction. The high rates of satisfaction in both cohorts are in line with results after other palliative cancer treatments despite high morbidity rates and poor overall survival.…”
Section: Discussionsupporting
confidence: 92%
“…10,11 In agreement with our results, both studies showed an association between significant improvements in HRQOL and satisfaction with treatment outcomes. 10,11 In addition, Hamilton et al 10 also showed no relation between the occurrence of adverse events (major or minor) and satisfaction. The high rates of satisfaction in both cohorts are in line with results after other palliative cancer treatments despite high morbidity rates and poor overall survival.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of the original studies included in the systematic review were of “low quality” and based on small patient samples, likely leading to overly simplified prediction models based on a single or a few prognostic indicators. More recently, several studies identified that a higher degree of baseline disability is associated with increased improvement of functional outcome [ 20 , 36 38 ], while smoking [ 36 , 39 , 40 ] and psychiatric disease [ 20 , 41 ] were associated with an unfavorable outcome. Athiviraham et al[ 20 ] reported that higher BMI was associated with less functional improvement, while Pearson et al [ 36 ] reported no difference in function between patients with BMI greater than or equal to 30 and those with a BMI below 30.…”
Section: Discussionmentioning
confidence: 99%
“…comes of conservatively and surgically managed patients with lumbar spinal stenosis have been reported at 4 to 5 years postoperatively. 13,20,28 A recent trend has been to use prospectively collected clinical registries to evaluate the quality of lumbar spinal stenosis care and to optimize healthcare resource distribution. 4,8 A key field of investigation involves identification of preoperative factors and/or patient characteristics that may affect patient-reported outcomes after surgical intervention for lumbar spinal stenosis.…”
mentioning
confidence: 99%